Use of memristor-based chaotic circuits in AM-DCSK and FM-DCSK modulation - Sahin, Muhammet Emin; Kolumban, Geza; Hamamci, Serdar Ethem; Guler, Hasan (Iop Publishing Ltd, 2023)
In this paper, digital communications systems are built by taking advantage of hyperchaotic circuits implemented with an active flux-controlled memristor. The signals produced by these hyperchaotic circuits with rich chaotic dynamics obtained by replacing the nonlinear element with the memristor in the Chua circuit and the Wien bridge oscillator are used as carriers in digital communications systems. The dynamic behavior of memristor-based hyperchaotic circuits has a high degree of disorder. Therefore, they offer better system performance in many practical applications such as broadband signal generation, encryption and secure communications compared to the already used ordinary chaotic systems. To demonstrate the excellent system performance of memristor-based chaotic circuits, they are applied to two variants of differential chaos shift keying (DCSK) communications schemes. Both the Amplitude Modulated Differential Chaos Shift Keying (AM-DCSK) and Frequency-modulated differential chaos shift keying (FM-DCSK) have been considered. The Bit Error Rate (BER) performances of the proposed AM-DCSK and FM-DCSK systems are evaluated in an Additive White Gaussian Noise (AWGN) channel.
Keywords: hyperchaotic circuit; nonlinear dynamics; chaos; memristor; memristor-based chaotic circuits; chaos-based modulation schemes; DCSK